DESIGN OF MODERN CLOTHING BASED ON THE TRANSFORMATION OF NATURAL SOURCES OF INSPIRATION - KRASNIUK , L.; HORNYI, P.; TROYAN , O. M. (Art and Design, 2024)
Purpose. The purpose of this research work is to develop new models of clothes in the artistic system «collection» using natural sources of inspiration based on the application of the composition rules and methods of artistic design of products. Methodology. The basic principles of the systematic approach to artistic design of the author creative collection such as literary analytical research and associative stylization of the source of creativity were used in the process. Results. The article shows that the development of the creative concept envisages the choice of the inspiration source which occupies the central place in the artistic designing of the author’s clothing collections. A compositional analysis of the source of inspiration – wild dried flowers – was carried out. The choice of compositional elements, principles and means of connection of the author’s clothing collection is substantiated. The transformation of the source of inspiration into forms of modern clothing was carried out. Various options for artistic and compositional solutions of clothing collections based on one source of inspiration have been developed. In the material, an ensemble of women’s clothing was made and its approbation was carried out in the conditions of contests of young clothing designers and scientific and practical conferences. Scientific novelty. The characteristic artistic and compositional features of the source of inspiration – dried wild flowers – have been studied and highlighted, and the principles of their use in the design of modern women’s clothing collections have been determined. Practical significance. Author’s collections of women’s clothing have been developed using the artistic and compositional features of wild dried flowers and modern fashion trends. The materials of this study can be reflected in lecture courses on the disciplines «Fundamentals of clothing harmonization» and «Artistic construction of design objects».